The The Relationship Between The Intensity Of Instagram Usage And Narcissistic Behavior In Generation Z - Milawati; Pahruddin (Journal of Political and Development Issue, 2025)
This study examines the relationship between Instagram usage intensity and narcissism behavior among Journalism students belonging to the Generation Z group. This research utilizes a quantitative approach with an explanatory quantitative research type. Explanatory quantitative research aims to explain the relationship, difference, or influence of one variable with another. The sample for this study comprised Journalism students from UIN Alauddin, batches 2016-2018, belonging to the Generation Z group. The sample was determined using probability sampling. The total sample size in this study was 166 people. The results showed that the intensity of Instagram use has a very low relationship with narcissistic behavior among Journalism students at UIN Alauddin, with a correlation coefficient value of 0.079, which falls within the range of 0.00 to 0.199. Although the direction of the relationship is positive, the contribution of the Instagram usage variable to narcissistic behavior is only 0.6%, thus its influence is considered very small.